Seasonal Occurrence and Distribution of Thunderstorm over Lokoja, Kogi State, Nigeria - E.B Audu; A Abenu; S.D Francis; A.I Agye; D.S. Rizama (ESUT JOURNAL OF SOCIAL SCIENCES, 2024)
The aim of the study was to ascertain the seasonal occurrence and distribution of thunderstorm (TS) in Lokoja. Data on monthly TS occurrence from 1980-2020 were obtained from the Nigerian Meteorological Agency (NiMet), Abuja and analysed for this study. Various statistical methods were developed and applied. Results showed the total monthly and inter-annual mean TS was 78 with 6 as the mean of mean. The major monthly mean occurrence was between April (average of 06) and October (average of 09). Lowest occurrence was observed in January and December, while highest of 14 was recorded in August and September. Highest positive mean deviation was 08 (August and September); least was 03 (May and October); highest negative mean deviation was -6 (January, February & December) with the least of -5 (March & November). Highest inter-annual mean TS of 08 occurred in 10 years with lowest of -2 (1997). Highest positive mean TS occurred in 10 years; while the least positive mean occurred in 1982 (04). Frequency count of mean TS occurrence showed 7 has the highest (17 years); while the least was 4 and -2 occurring once each. On inter-annual mean deviation, positive deviation occurred most frequently (18 years), followed by zero (0), 14 years; and lastly, negative deviation (9 years). Highest inter-annual positive mean deviation was 2; lowest was 1; while highest negative mean deviation was -9 with -1 as the least. Dry season percentage (%) occurrence was 4.8 % and 95.2 % for rainy season. Mean decadal TS signified 82.4 (2000-2009) as highest, while 75.3 (1990-1999) was the least; a projection to the 5th decade, 2020-2029 was 77.8. In conclusion, wet TS is the major type in this area. It was therefore recommended that, TS forecast should be included in the Seasonal Climate Prediction (SCP) and daily weather forecast by the Nigerian Meteorological Agency (NiMet); and TS occurrence should serve as early warning system of severe weather.